Volatile Constituents of Taxus baccata L. Leaves from Western and Southern Turkey - Yasar, Samim (Asian Journal of Chemistry, 2013)
The fresh leaves of Taxus baccata L., growing in western (Aegean region) and southern (Mediterranean region) Turkey, on hydrodistillation, gave 0.03 and 0.04 % oil on dry basis, respectively. After GC and GC/MS analysis, 45 compounds (representing 97.4 % of the oil) and 56 components (representing 98 % of the oil) were identified for T. baccata L. leaves collected from western and southern Turkey. The predominant constituents were 1-octen-3-ol (32.4 %), (E)-2-hexen-1-ol (8.2 %), caryophyllene oxide (7.2 %) and hexahydrofarnesyl acetone (6.8 %) in the oil of T. baccata L. from western Turkey and 1-octen-3-ol (20.7 %), 1-hexanol (10.9 %) and (E)-2-hexen-1-ol (7.3 %) in the oil of T. baccata L. from southern Turkey. The most abundant components of T. baccata L. oil samples from both regions of Turkey were alcohols with their contents being 62.4 and 54.1 %, respectively.